Penatalaksanaan Pneumonia Pada Balita Usia 7 Bulan dengan Pendekatan Kedokteran Keluarga - Nada Naqiyya; Fukrapti; Aila Karyus (Medula, 2022)
Pneumonia is a disease that attacks the lower respiratory tract by pathogens. The most common causes in toddlers and children are viruses and bacteria. This article is a form of implementing family doctor services for patients by identifying risk factors, clinical problems, management and prevention efforts for patients based on a patient-centered and family problem solving framework. This study is a case report using primary data obtained through alloanamnesis, physical examination, home visits to complete family and psychosocial data, as well as environmental conditions. The assessment is based on a holistic diagnosis from the beginning, process and end of the study both quantitatively and qualitatively. A 7 month old toddler patient with a diagnosis of pneumonia. In this case, the internal factor that played a role in the patient was the patient's age, which was 7 months. External factors, namely the lack of family knowledge about pneumonia, its complications and the environment that has trigger factors. These patients were then given pharmacological and non-pharmacological interventions according to evidence-based medicine. The evaluation results showed an improvement in the patient's clinical condition and increased family knowledge about pneumonia. The diagnosis and management of this patient have been carried out according to the guidelines. Changes in behavior and knowledge of patients and their families are seen after interventions that are patient centered and family approach.